Phylogeny and cryptic diversification in Southeast Asian flying geckos - Brown, R.; Siler, C.D; Grismer, L.L; Das, I.; McGuire, J.A (Elsevier Ltd, 2012)
The closed-canopy forests of Southeast Asia are home to an impressive number of vertebrates that have independently evolved morphologies that enhance directed aerial descent (gliding, parachuting). These assemblages include numerous mammal, frog, snake, and lizard clades. Several genera of gekkonid liz- ards, in particular, have evolved specialized structures such as cutaneous expansions, flaps, and midbody patagia, that enhance lift generation in the context of unique gliding and parachuting locomotion. The genus Ptychozoon represents arguably the most morphologically extreme, highly specialized clade of glid- ing geckos. Despite their notoriety and celebrated locomotor ability, members of the genus Ptychozoon have never been the subject of a species-level molecular phylogenetic analysis. In this paper, we utilize molecular sequence data from mitochondrial and nuclear gene fragments to estimate the evolutionary relationships of this unique group of flying geckos. Capitalizing on the recent availability of genetic sam- ples for even the rarest of known species, we include the majority of known taxa and use model-based phylogenetic methods to reconstruct their evolutionary history. Because one species, P. kuhli , exhibits an unusually wide distribution coupled with an impressive range of morphological variation, we addi- tionally use intensive phylogeographic/population genetic sampling, phylogenetic network analyses, and Bayesian species delimitation procedures to evaluate this taxon for the possible presence of cryptic evolutionary lineages. Our results suggest that P. kuhli may consist of between five and nine unrecog- nized, distinct species. Although we do not elevate these lineages to species status here, our findings sug- gest that lineage diversity in Ptychozoon is likely dramatically underestimated.